Preparation method of high-purity aluminum magnesium oxide nano material precursor

By reacting alumina and magnesium oxide in nitric acid, and adding citric acid, ethylene glycol and glycine to form colloids, the problems of carbon residue and low purity in nanomaterials are solved, and high purity and uniformity of nanometers are achieved Material preparation simplifies calcining conditions and reduces costs.

CN119118171APending Publication Date: 2024-12-13SICHUAN YANRUI ELECTRONIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411107621.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-13
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In the existing nanomaterial synthesis methods, there are problems such as carbon residue, easy agglomeration, uneven particle size distribution, calcination under atmosphere and low material purity, resulting in poor performance and high cost.

Method used

A high-purity aluminum oxide magnesium nanomaterial precursor is used to prepare a precursor of high-purity aluminum oxide. By reacting alumina and magnesium oxide in nitric acid, citric acid, ethylene glycol and glycine are added, and then evaporate and hydrolyze after forming colloids to remove soluble impurities and carbon-containing Organic substances provide high-purity nanomaterial precursors.

Benefits of technology

It improves the purity and uniformity of nanomaterials, simplifies calcination conditions, reduces costs, and achieves high-temperature calcination in an air environment, improving the performance and production efficiency of nanomaterials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118171A_ABST
    Figure CN119118171A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-purity aluminum magnesium oxide nano material precursor, and relates to the technical field of nano material preparation. Soluble impurity ions, carbonaceous organic matters and the like are removed through hydrolysis reaction to obtain the precursor without impurities and carbonaceous substances, so that the purity of the nano material is improved, the defects of the existing nano material are overcome, and the performance of the nano material is improved. The hydrolysis reaction can be realized without adjusting the pH value, and the obtained precursor has the characteristics of better chemical activity and uniform components compared with the material prepared by the traditional method, so that the nanomaterial has more complete grain morphology and more uniform components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano material preparation, and in particular to a method for preparing a high-purity aluminum magnesium oxide nano material precursor. Background Art

[0002] Nanomaterials are ultrafine powders, generally referring to powders with a particle size of less than 100 nanometers. At present, nanomaterials are generally synthesized by solution method, gas phase method, electrochemical method, etc. Among them, the solution method is one of the most commonly used methods for synthesizing nanomaterials, which is divided into sol-gel method, precipitation method and liquid phase synthesis method. The advantages of the solution method are simple operation, conducive to large-scale synthesis, and the ability to obtain nanomaterials at a lower temperature. However, in order to obtain nanomaterials with smaller grain sizes, nanomaterials synthesized by the solution method usually need to be calcined at low temperatures, which will cause uneven particle size distribution and irregular morphology, as well as the problem that organic matter cannot be fully burned during the calcination process, which will lead to residual trace carbon elements in the nanomaterials. For some sensitive materials, the residual trace carbon elements will have an adverse effect on the electrical and optical properties of the material. The gas phase method is another commonly used synthesis method for nanomaterials, which includes thermal evaporation, physical vapor deposition and chemical vapor deposition. Compared with the solution method, the nanomaterials synthesized by this method have higher purity and better crystal structure. However, this method needs to be carried out under high vacuum and high temperature conditions, the synthesis process is relatively complicated, and the cost is high. The electrochemical method is a selective synthesis method that controls the size and morphology of particles by controlling voltage and current. This method is suitable for nanomaterials with complex crystal structures and special morphological requirements. Since this method takes a long time to synthesize nanomaterials and involves electrolytes, electrodes and other issues during the synthesis process, it is relatively complicated and not suitable for large-scale production.

[0003] As for the existing methods for synthesizing nanomaterials, the solution method is the most commonly used method. However, in the synthesis of nanomaterials, the sol-gel method is not easy to mass produce. Although the biggest advantage is the low calcination temperature, the crystal morphology of the nanomaterial is not very ideal. In addition, the carbon element in the material is not easy to be completely discharged. It is necessary to calcine and discharge carbon in an oxygen atmosphere, and there will be trace amounts of carbon elements remaining. Increasing the calcination temperature to discharge carbon is a feasible method, but it will also lead to abnormal growth of the grain size, and the ideal nanomaterial size cannot be obtained. The biggest advantage of the precipitation method is low cost and large-scale production, but since it is difficult to achieve precise control of the pH control, the obtained material still has problems in terms of uniformity. The advantages of the liquid phase synthesis method are easy operation, simple synthesis process, uniform particle size, controllable particle size, less pollution, and can avoid or reduce the hard agglomeration phenomenon that is easy to appear in the liquid phase, and low cost. However, the disadvantages are that the composition is not easy to be uniform, the particles are easy to agglomerate, and the powder particle size distribution is wide.

[0004] At present, how to solve the problems of carbon residue, easy agglomeration, uneven particle size distribution, calcination under atmosphere, and low material purity in the synthesis of nanomaterials is an urgent problem to be solved. The raising of this problem has put forward more urgent requirements for technicians in the field to develop nanomaterials with superior performance and low cost. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a high-purity aluminum magnesium oxide nanomaterial precursor, which can remove soluble impurity ions and carbon-containing organic matter, thereby improving the purity of the nanomaterial and thus improving the shortcomings of existing nanomaterials.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows: A method for preparing a high-purity aluminum magnesium oxide nanomaterial precursor comprises the following steps: Step 1, adding aluminum oxide and magnesium oxide in a molar ratio of 1: (0-1) to nitric acid for reaction, then heating and stirring the reactants in a water bath at 80-90° C. until the aluminum oxide and magnesium oxide are completely dissolved to obtain an initial solution, and adjusting the pH value of the initial solution to 4-5.5; Step 2, filter the initial solution, add citric acid solution; then add 0.1-5% ethylene glycol solution with a molar mass fraction, stir until mixed; then add 0-3% glycine solution with a molar mass fraction, stir until mixed, to obtain a mixed solution; Step 3, evaporating the mixed solution into a viscous colloid. Since the metal ions (aluminum / magnesium ions) preferentially combine with the citric acid solution in step 2, the probability of the metal ions connecting with the carbon element in the colloid (organic matter) is reduced; Step 4, drying the colloid into foam, and then crushing and sieving the foam to obtain organic foam powder; Step 5: Place the organic foam powder in deionized water for hydrolysis, and then filter, wash and dry to obtain a high-purity aluminum oxide magnesium nanomaterial precursor. The hydrolysis can directly promote the breaking of the chemical bonds between the metal ions (aluminum / magnesium ions) in the metal salt organic matter and the organic matter, wherein the metal ions are converted into complexes or crystalline hydrates of the corresponding hydroxides (Al(OH)3, Mg(OH)2) to form precipitates, and then filter and wash to remove soluble impurities and organic matter (carbon-containing substances) dissolved in water.

[0007] Furthermore, in step 1, the molar ratio of amol aluminum oxide, bmol magnesium oxide and nitric acid is a:b:(6a+2b).

[0008] Furthermore, in step 1, deionized water is used as a medium to carry out the reaction of aluminum oxide, magnesium oxide and nitric acid.

[0009] Furthermore, in step 5, the reaction equation for hydrolysis is as follows: Mg n Al m (CH6O7) x (NO3) 3m+2n-x +(3m+2n)H2O→nMg(OH)2+mAl(OH)3+ xC6H5O7 - + (3m+2n-x)NO3 - +(3m+2n) / 2 H + ; Mg n Al m (CH6O7) x (NO3) 3m+2n-x It is the chemical formula of the polymer in the organic foam powder.

[0010] Furthermore, in step 2, the molar concentration of the citric acid solution is 0.5-1.5 mol / L.

[0011] Furthermore, in step 2, the molar ratio of citric acid in the citric acid solution to aluminum ions and magnesium ions in aluminum oxide and magnesium oxide is 2-2.5:1:1.

[0012] Furthermore, in step 3, the evaporation time is 36-72 hours.

[0013] Furthermore, in step 4, the drying temperature is 100-180° C., the drying time is 5-9 hours, and the mesh size of the sieve used for sieving is 80-300.

[0014] Furthermore, in step 5, the volume of deionized water is 8-40 times the volume of the organic foam powder.

[0015] Furthermore, in step 5, the hydrolysis time is 1.5-6h.

[0016] When synthesizing nanomaterials using the traditional liquid phase method, the inorganic salt ions in each chemical reaction are connected to the carbon bonds in the organic matter. The molecular bonds formed between the metal elements and the organic matter are ionic bonds or covalent bonds. During the synthesis process, the carbon element will always form a bond with the metal element. Whether it is in the process of forming a sol-gel or in the process of polymerization, the chemical bond always exists. Therefore, during the calcination of the nanomaterial precursor, if there is insufficient oxygen, residual organic matter or residual carbon may appear. In addition, calcination in an air atmosphere may also result in insufficient reaction, and impurities and other carbon-containing substances cannot be removed.

[0017] The present invention obtains a solution containing aluminum and magnesium elements by reacting nitric acid with aluminum oxide and magnesium oxide and then heating; then adding multiple solutions, on the one hand, achieving atomic-level uniformity, ensuring that the electrical and mechanical properties of the synthesized nanomaterials will not be inconsistent in the microscopic and macroscopic dimensions due to uneven mixing, and on the other hand, forming a network of organic matter, while using citric acid to remove metal elements existing in ions through bond valence; then evaporating the organic matter in the mixed solution into a colloid, further foaming and polymerization reaction to generate a polymer, crushing the foamed material into tiny powders, and then hydrolyzing the powder. Since the hydrolysis conditions occur in an aqueous solution, it is not necessary to add acid and alkali to adjust the pH value in this process, and the metal elements are also uniformly mixed at the atomic level, so the obtained hydrolyzed material has atomic-level uniformity. After hydrolysis, a nano white precipitate containing aluminum and magnesium ions (Al(OH)3, Mg(OH)2, which is an inorganic high-activity mixed material) will be obtained, which can be removed by washing with water. During the hydrolysis process, water-soluble impurities (such as Na, K ions and their compounds) can also be removed, and organic matter and carbon-containing substances that are not completely foamed but remain can also be cleaned and removed to obtain a high-purity precursor.

[0018] The present invention removes impurities, organic matter or carbon elements through a hydrolysis reaction, and can improve the purity of the nanomaterial formed by high-temperature calcination of the precursor. This is because by breaking the chemical bond between the carbon element and the metal element in the precursor in advance and removing the carbon element, the precursor purity is higher and the uniformity is better, thereby making the nanomaterial purity higher and the uniformity better. During the later high-temperature calcination, the OH bond in the corresponding complex or crystalline hydrate of the aluminum and magnesium ions in the precursor is broken, thereby obtaining a nanomaterial containing the corresponding metal oxide, and the calcination temperature and conditions are milder, and the calcination process is faster.

[0019] The present invention also adds ethylene glycol and glycine for two reasons. First, in the process of forming organic matter, there may be a situation where metal ions cannot combine with citric acid to form a bond, and ethylene glycol and glycine can assist the combination of the two. Second, the addition of ethylene glycol and glycine can promote the polymerization reaction of the colloid during the drying process, so that the foamed foam can have more and smaller pores and more uniform pores. In addition, the covalent bond energy between polymer macromolecules in the colloid can be reduced, so that the metal elements connected to the carbon bonds of the polymer can form small particles of inorganic matter during the hydrolysis reaction.

[0020] Compared with the prior art, the present invention has the following beneficial effects: The present invention removes soluble impurity ions and carbon-containing organic matter through a hydrolysis reaction to obtain a precursor free of impurities and carbon-containing substances, thereby improving the purity of the nanomaterial, thereby improving the shortcomings of existing nanomaterials and improving the performance of the nanomaterial.

[0021] Since the hydrolysis reaction of the present invention does not need to adjust the pH to be realized, the obtained precursor has better chemical activity and uniform composition than the material prepared by the traditional method, so that the nano material grain morphology is more complete and the composition is more uniform.

[0022] The process of the present invention is simple to operate, low in cost and high in production efficiency. Different from the traditional process of calcination in oxygen atmosphere, the calcination conditions of the nanomaterials in the later stage can be simplified, and nanomaterials with higher purity can be obtained by calcination in air atmosphere and low temperature, which is beneficial to the improvement of production efficiency of enterprises. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is the XRD pattern of the precursor prepared in Example 1. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] In the embodiment of the present invention, in step 1, deionized water is used as a medium to react aluminum oxide, magnesium oxide and nitric acid, and deionized water is added until the molar concentration of aluminum ions in the reactants is 0.5-1.5 mol / L.

[0026] As a preferred embodiment of the present invention, the present invention provides a method for preparing a high-purity aluminum oxide nanomaterial precursor, comprising the following steps: Step 1, add 1 mol of aluminum oxide to 6 mol of nitric acid for reaction, then heat and stir the reactants in a water bath at 80° C. until the aluminum oxide is completely dissolved to obtain an initial solution, and adjust the pH value of the initial solution to 4.51; Step 2, filter the initial solution, add 2.06 mol of citric acid solution (1 mol / L); then add ethylene glycol solution with a molar mass fraction of 2.5%, stir for 1-2 hours until the mixture is uniformly mixed; then add glycine solution with a molar mass fraction of 2%, stir for 1-2 hours until the mixture is uniformly mixed, and obtain a mixed solution; Step 3, placing the mixed solution in a water bath and evaporating for about 48 hours to obtain a viscous colloid; Step 4, placing the colloid in an oven and drying it at 150° C. for 8 hours to obtain foam, and then crushing the foam and sieving it through 100 mesh to obtain organic foam powder; Step 5: Place the organic foam powder into deionized water with a volume 20 times that of the organic foam powder for hydrolysis for 2 hours, and then filter, wash and dry to obtain a high-purity aluminum oxide nanomaterial precursor.

[0027] As a preferred embodiment of the present invention, the present invention provides a method for preparing a high-purity aluminum oxide magnesium nanomaterial precursor, comprising the following steps: Step 1, add 1 mol of aluminum oxide and 1 mol of magnesium oxide to 8 mol of nitric acid for reaction, then heat and stir the reactants in a water bath at 85° C. until the aluminum oxide and magnesium oxide are completely dissolved to obtain an initial solution, and adjust the pH value of the initial solution to 4.15; Step 2, filter the initial solution, add 3.06 mol of citric acid solution (0.5 mol / L); then add 0.1% ethylene glycol solution, stir for 1-2 hours until mixed evenly, and stir for another 1-2 hours until mixed evenly to obtain a mixed solution; Step 3, placing the mixed solution in a water bath and evaporating for about 72 hours to obtain a viscous colloid; Step 4, placing the colloid in an oven and drying it at 130° C. for 9 hours to obtain foam, and then crushing the foam and sieving it through 200 mesh to obtain organic foam powder; Step 5: Place the organic foam powder into deionized water with a volume 30 times that of the organic foam powder for hydrolysis for 5 hours, and then filter, wash and dry to obtain a high-purity aluminum oxide nanomaterial precursor.

[0028] As a preferred embodiment of the present invention, the present invention provides a method for preparing a high-purity aluminum oxide magnesium nanomaterial precursor, comprising the following steps: Step 1, add 1 mol of aluminum oxide and 0.95 mol of magnesium oxide to 7.9 mol of nitric acid for reaction, then heat and stir the reactants in a 90° C. water bath until the aluminum oxide is completely dissolved to obtain an initial solution, and adjust the pH value of the initial solution to 5.25; Step 2, filter the initial solution, add 2.95 mol of citric acid solution (1.5 mol / L); then add 1.5% ethylene glycol solution, stir for 1-2 hours until the mixture is uniformly mixed; then add 2.5% glycine solution, stir for 1-2 hours until the mixture is uniformly mixed, and obtain a mixed solution; Step 3, placing the mixed solution in a water bath and evaporating for about 36 hours to obtain a viscous colloid; Step 4, placing the colloid in an oven and drying it at 160° C. for 6 hours to obtain foam, and then crushing the foam and sieving it through 200 mesh to obtain organic foam powder; Step 5: Place the organic foam powder into deionized water with a volume 8 times that of the organic foam powder for hydrolysis for 3 hours, and then filter, wash and dry to obtain a high-purity aluminum oxide magnesium nanomaterial precursor.

[0029] As a preferred embodiment of the present invention, the present invention provides a method for preparing a high-purity aluminum oxide magnesium nanomaterial precursor, comprising the following steps: Step 1, add 1 mol of aluminum oxide and 1 mol of magnesium oxide to 8 mol of nitric acid for reaction, then heat and stir the reactants in a 90° C. water bath until the aluminum oxide and magnesium oxide are completely dissolved to obtain an initial solution, and adjust the pH value of the initial solution to 4.78; Step 2, filter the initial solution, add 3.05 mol of citric acid solution (2 mol / L); then add 1.5% ethylene glycol solution, stir for 1-2 hours until the mixture is uniformly mixed; then add 0.5% glycine solution, stir for 1-2 hours until the mixture is uniformly mixed, and obtain a mixed solution; Step 3, placing the mixed solution in a water bath and evaporating for about 72 hours to obtain a viscous colloid; Step 4, placing the colloid in an oven and drying it at 120° C. for 9 hours to obtain foam, and then crushing the foam and sieving it through 100 mesh to obtain organic foam powder; Step 5: Place the organic foam powder into deionized water with a volume 40 times that of the organic foam powder for hydrolysis for 4 hours, and then filter, wash and dry to obtain a high-purity aluminum oxide magnesium nanomaterial precursor.

[0030] The particle size and impurity content of the nanomaterials prepared in Examples 1 to 4 were tested by X-ray diffraction. The test results are shown in Table 1 below.

[0031] Table 1

[0032] It can be seen from the data in Table 1 that the precursor of the nanomaterial prepared by the present invention has good particle size distribution, high purity, less residual impurities such as carbon element, and can be calcined in an air environment, which significantly improves the quality and stability of the product. In addition, the production raw materials are cheap, and the preparation process is compatible with traditional processes, which is conducive to improving the production efficiency of the enterprise.

[0033] like Figure 1 As shown, the precursor prepared in Example 1 contains a complex of metal hydroxide or a complex substance containing crystal water, and does not contain carbon-containing substances.

[0034] Finally, it should be noted that the above embodiments are only preferred embodiments of the present invention to illustrate the technical solutions of the present invention, rather than limiting them, and certainly not limiting the patent scope of the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. In other words, any changes or modifications made to the main design concept and spirit of the present invention that have no substantive significance, and the technical problems they solve are still consistent with the present invention, should be included in the protection scope of the present invention. In addition, the direct or indirect application of the technical solutions of the present invention in other related technical fields is also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a high-purity aluminum oxide magnesium nanomaterial precursor, characterized in that: The following steps are involved: Step 1, adding aluminum oxide and magnesium oxide in a molar ratio of 1: (0-1) to nitric acid for reaction, then heating and stirring the reactants in a water bath at 80-90° C. until the aluminum oxide and magnesium oxide are completely dissolved to obtain an initial solution, and adjusting the pH value of the initial solution to 4-5.5; Step 2, filter the initial solution, add citric acid solution; then add 0.1-5% ethylene glycol solution with a molar mass fraction, stir until mixed; then add 0-3% glycine solution with a molar mass fraction, stir until mixed, to obtain a mixed solution; Step 3, evaporating the mixed solution into a viscous colloid; Step 4, drying the colloid into foam, crushing and sieving the foam to obtain organic foam powder; Step 5: Place the organic foam powder in deionized water for hydrolysis, and then filter, wash and dry to obtain a high-purity aluminum oxide magnesium nanomaterial precursor.

2. The method for preparing a high-purity aluminum oxide magnesium nanomaterial precursor according to claim 1, characterized in that: In step 1, the molar ratio of amol aluminum oxide, bmol magnesium oxide and nitric acid is a:b:(6a+2b).

3. The method for preparing a high-purity aluminum oxide magnesium nanomaterial precursor according to claim 1, characterized in that: In the step 1, deionized water is used as a medium to carry out the reaction of aluminum oxide, magnesium oxide and nitric acid.

4. The method for preparing a high-purity aluminum oxide magnesium nanomaterial precursor according to claim 1, characterized in that: In the step 5, the reaction equation for hydrolysis is as follows: <h2 style=";text-align:left;direction:ltr">Mg<h2 style=";text-align:left;direction:ltr"> n <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> m <h2 style=";text-align:left;direction:ltr"> (CH6O7)<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> (NO3)<h2 style=";text-align:left;direction:ltr"> 3m+2n-x <h2 style=";text-align:left;direction:ltr"> +(3m+2n)H2O→nMg(OH)2+mAl(OH)3+ xC6H5O7<h2 style=";text-align:left;direction:ltr"> - <h2 style=";text-align:left;direction:ltr"> + (3m+2n-x)NO3<h2 style=";text-align:left;direction:ltr"> - <h2 style=";text-align:left;direction:ltr"> +(3m+2n) / 2 H<h2 style=";text-align:left;direction:ltr"> + <h2 style=";text-align:left;direction:ltr"> ; Mg n Al m (CH6O7) x (NO3) 3m+2n-x It is the chemical formula of the polymer in the organic foam powder.

5. The method for preparing a high-purity aluminum oxide magnesium nanomaterial precursor according to claim 1, characterized in that: In step 2, the molar concentration of the citric acid solution is 0.5-1.5 mol / L.

6. The method for preparing a high-purity aluminum oxide magnesium nanomaterial precursor according to claim 1, characterized in that: In step 2, the molar ratio of citric acid in the citric acid solution to aluminum ions and magnesium ions in aluminum oxide and magnesium oxide is 2-2.5:1:

1.

7. The method for preparing a high-purity aluminum oxide magnesium nanomaterial precursor according to claim 1, characterized in that: In step 3, the evaporation time is 36-72 hours.

8. The method for preparing a high-purity aluminum oxide magnesium nanomaterial precursor according to claim 1, characterized in that: In the step 4, the drying temperature is 100-180° C., the drying time is 5-9 hours, and the mesh number of the sieve used for sieving is 80-300.

9. The method for preparing a high-purity aluminum oxide magnesium nanomaterial precursor according to claim 1, characterized in that: In step 5, the volume of deionized water is 8-40 times the volume of the organic foam powder.

10. The method for preparing a high-purity aluminum oxide magnesium nanomaterial precursor according to claim 1, characterized in that: In step 5, the hydrolysis time is 1.5-6h.